Bridging the Gap Between the Theory and Practice of Software Test Automation - Budnik, Christof J.; Chan, Wing Kwong; Kapfhammer, Gregory M. (2010 ACM/IEEE 32nd International Conference on Software Engineering, 2010)
In software development practice, testing often accounts for as much as 50% of the total development effort. It is therefore imperative to reduce the cost and improve the effectiveness of software testing by automating the testing process. In the past decades, a substantial amount of research effort has been invested into the development and study of automatic test case generation, automatic test oracles, and other (semi-)automated testing techniques. As the theory and practice of software testing becomes more mature, a deeper and more meaningful automation of the testing process is possible. Therefore, the automation of various testing activities is now becoming an integral part of industrial practice. In response to and in support of these exciting developments, the 5th Workshop on the Automation of Software Test provides a publication forum that bridges the gap between the theory and practice of automated testing.